PENINGKATAN KEMAMPUAN PRONUNCIATION SISWA SMK KARYABHAKTI BREBES DENGAN MENGGUNAKAN WEBSITE WWW.ESLFAST.COM - Syaefani Arif Romadhon; Iin Indrayanti; Mutiarawati Mutiarawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
In order to increase students' confidence in speaking activities, it is necessary to be equipped with pronunciation. With sufficient pronunciation, the speaking practiced by students becomes acceptable and well understood. One of the learning media that provides pronunciation facilities is the website www.eslfast.com. Students can choose learning materials from basic to advanced levels. The advantage of this website is that there are various choices of text dialogues and monologues. PKM was held on Wednesday, November 10, 2021, 10:00-12:00 WIB at SMK Karya Bhakti, Brebes using lecture and practical methods. Students are introduced to and also practices related to the use of eslfast.com website using their respective gadgets. The enthusiasm of students in the PKM activity was high, around 85% of students thought the importance of learning pronunciation using the website. It is hoped that this PKM activity will increase students' motivation to learn pronunciation. At the end of the session students were given an additional demonstration of SEFT Hypnotherapy which was beneficial for physical and spiritual health.